Peran Organizational Citizenship Behavior dalam Memediasi Pengaruh Kompetensi dan Budaya Organisasi terhadap Kinerja Karyawan - Soegeng Wahyoedi; Hery Winoto Tj; Guntur Novizal (IPM2KPE, 2022)
This study aims to determine the role of organizational citizenship behavior in mediating the influence of competence and organizational culture on employee performance. This research method is descriptive quantitative. The population in this study are credit marketing officers, employees of Maybank Finance for the marketing department. This study uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.3 software. The results showed that competence, organizational culture and organizational citizenship behavior each had a significant and positive effect on employee performance. The influence of these three variables is 71% and the rest is influenced by other variables not examined by 29%. In conclusion, organizational citizenship behavior variable has a role in mediating the influence of competence on employee performance and organizational citizenship behavior variable also mediates the influence of culture on employee performance. Keywords: Organizational Culture, Employee Performance, Competence, Organizational Citizenship Behavior